Ab initio study on the spectroscopic and radiative properties of the low-lying states of the radium monoiodide RaI molecule. (July 2022) - Osika, Yuliya; Shundalau, Maksim; Han, Yong-Chang
Highlights: Fock-space relativistic coupled cluster calculations. Potential energy curves. Molecular spectroscopic constants. Radiative properties. Laser cooling scheme. Abstract: The main focus of this study is the radium monoiodide RaI molecule, which is a promising candidate for direct laser cooling. To support this statement we calculated the potential energy curves of the ground and five low-lying excited states using the Fock-space relativistic coupled cluster theory. Calculations of spectroscopic properties including electronic term energies, equilibrium internuclear distances, transition and permanent dipole moments, vibrational energies and harmonic vibrational frequencies, Frank–Condon factors and radiative lifetimes were also performed. Based on the results we conclude that RaI molecule can be used for direct laser cooling and propose the probable laser cooling scheme. This work continues the series of research of radium monohalides and includes the comparison of results with previously studied RaCl, RaF and RaBr molecules. It can provide an understanding of trends in spectroscopic and radiative properties of this alkaline earth metal monohalides series. Graphical abstract: Image, graphical abstract